The Tendency of Economic Convergence Among Regions in Banten Province - Pramesti, Maharani; Ahmed, Muhammad Ali (Fakultas Ekonomi dan Bisnis Islam, 2024)
The province of Banten, as one of the developed provinces in Java Island, is expected to be able to drive the economy of other provinces. However, the good economic level in Banten Province is not followed by an even distribution of income among its regions. The Williamson Index value indicates that the inequality in Banten Province is still relatively high. Nevertheless, at some point, relatively underdeveloped regions can catch up with the more developed ones, so that the level of income among regions becomes relatively similar. This phenomenon is called economic convergence. This study aims to identify the tendency of economic convergence among regions in Banten Province and analyze the variables influencing economic growth to encourage economic convergence using a panel data regression approach. The research results indicate a tendency of economic convergence in Banten Province, with variables such as the number of poor people, the Human Development Index (HDI), and the unemployment rate playing significant roles in economic convergence.